An improvement of automated software fault injection tool for robustness / Mohd Daud Alang Hassan and Saiful Fadzli Salian. - Alang Hassan, Mohd Daud; Salian, Saiful Fadzli (2008)
This project is a continuation from earlier work involving the development of a software fault injection tool, called SFIT. A number of limitation is observed in the earlier version of SIFT in terms of the support for automated testing, the integration with a graphical user interface as well as the capabability to keep historical data. A new version of SFIT has been developed as a result. In order to evaluate its suitability and applicability as a general software testing tool, a number of experiments have been devised utilizing SFIT to perform robustness testing on a public domain commercial-off-the-shelves components for distributed shared memory manipulation library, called Jada. In doing so, a number of observation have also been made in terms of the robustness of Jada (i.e. in terms of whether or not Jada can be used in a highly available and safety critical systems).